Osteoporosis Awareness and Effecting Factors: A Descriptive Cross-Sectional Study - Oğuzhan Gökalp; Çiğdem Kaya; Yılmaz Kaya (Türk Osteoporoz Dergisi)
Objective: Osteoporosis is a chronic metabolic bone disease characterized by bone fragility and increased fracture risk. The prevalence of osteoporosis has increased because of demographic changes and lifestyle modifications. Osteoporotic fractures are associated with a previous fragility fracture. This study aimed to determine patients’ awareness levels regarding the prevention of new fractures and the necessary precautions for osteoporosis. Materials and Methods: This descriptive cross-sectional study included 112 patients with osteoporotic fractures who met the inclusion criteria. The effect level was 0.632, the confidence interval (a) was 0.05, and the power of the test (1-b) was 0.95 for 110 samples. The patient information form and osteoporosis awareness scale (OAS) were used for data collection. Results: Eighty-three patients (74.1%) were unaware that their fractures were osteoporotic, and 35.7% (n=40) had a history of previous fractures. The mean OAS total score of patients diagnosed with osteoporosis before fracture, those who had a family member diagnosed and treated with osteoporosis, and those who received education about osteoporosis was significantly higher. It was found that there was a moderate positive correlation between educational status and OAS total score (r=451; p<0.001). There was no difference in the OAS total score between patients with and without previous fractures (p=0.817). It was found that 53.5% of patients diagnosed with osteoporosis before the fracture still needed education about osteoporosis. Conclusion: The results showed that patient education successfully increased awareness but did not help develop positive preventive attitudes in patients. Repeated training is necessary for individuals at risk. Bone mineral densitometry scan rates are low even in patients with a history of fragility fractures. The awareness of orthopedic specialists regarding osteoporosis education and diagnosis should be increased. The dissemination of screening tests for early diagnosis of osteoporosis should be part of the public health agenda.